The Relationship between Local Wisdom and Islamic Against Ka’ombo in Buton’s Lambusango Forest - Sukiyawati; Muhammad Majid (Journal of Asian Wisdom and Islamic Behavior, 2024)
Forms of local wisdom are very diverse, starting from certain ceremonies, certain crafts, and certain activities that are considered beneficial for human survival. Local wisdom indeed aims to maintain the original characteristics of each region and is beneficial for the people in that region, but how does Islam assess this local wisdom? The relationship between local wisdom and the Islamic religion is mutually sustainable towards environmental preservation by using kaombo in the Lambusango Forest, Buton. This research was conducted using qualitative methods with the type of phenomenological research. According to Creswell, qualitative research arises in the background of natural situations in which many human behaviors and events occur. The Ka'ombo ritual is included in al 'urf al-khash, namely customs that apply in society and in certain areas, in this case a special tradition in the Buton Sultanate and which continues to be preserved by the Buton people until now. As for its validity from a syara' perspective, the Ka'ombo ritual is included in Al-'urf al-shahih, namely customs that apply in society that do not conflict with the texts (verses or hadith), do not eliminate their benefits, and do not bring harm to they.